Coconut hispine beetle Brontispa longissima (Gestro) (Coleoptera: Chrysomelidae) - Singh, S. P.; Rethinam, Ponniah (International Coconut Community Journal, 2004)
Coconut hispine beetle, Brontispa longissima (Gestro) was originally described from the Aru Islands (Maluku Province). It is native to Indonesia (Aru Islands, Maluku Province and possibly to Papua Province formerly known as Irian Jaya), and also to Papua New Guinea, including the Bismarck Archipelago, where it seldom causes serious problems. It has now spread widely in Asia, Australasia and Pacific Islands attacking not only coconut palm but also several other cultivated and wild palms. In recent times it has spread to Singapore, Vietnam, Nauru, Thailand, Maldives and Hainan Island (China). In the absence of natural antagonists it has become a very serious and devastating pest in new areas of its spread. It is feared that B. longissima will find its way from Maldives to Sri Lanka and southern parts of India to derail the economy of these important coconut-growing regions of the world. Thus emergency operations are necessary to try to decimate it down in the Maldives. A number of natural enemies such as Hispidophila (Haeckeliania) brontispae Ferriere, Ooncyrtus podontiae Gahan, Trichogrammatoidea nana Zehntner, Tetrastichus brontispae Ferriere, Asecodes hispinarum Boucek, Chrysonotomyia sp., Metarhizium anisopliae (Metchnikoff) Sorokin, Chelisoches morio Fabricius, Oecophylla smaragdina (Fabricious), mites on adults (Anoplocelaeno sp. and Celaenopsis sp.), geckoes, skinks, tree frog and unidentified bacterial pathogen have been recorded. Biological control by introduction and enhancement of parasitoids- A. hispinarum and T. brontispae has proved very effective. Similarly spray of improved strains of entomopathogenic fungus, M. anisopliae has proved effective. Exploratory surveys for parasitoids in the original home of B. longissima are suggested.